Effect of Rolling Deformation on Creep Properties of FeCrAl Alloys - Lai, Huan Sheng; Guo, Jingyu; Zhang, Shanglin; Yu, Xiaobin; Meng, Fanqiang; Zhao, Zilong; Zhou, Wenzhong (Frontiers in Energy Research, 2021)
FeCrAl alloy is one of the most promising nuclear fuel claddings among many accident tolerant fuel (ATF) materials due to its excellent oxidation resistance and good mechanical properties. However, the effect of process conditions on the creep properties of the FeCrAl alloy is not clear till now. In this paper, the impact of a process condition of hot-rolling on the creep properties of FeCrAl alloy was investigated using a nano-indentation creep test under a temperature of 350 ºC. The microanalysis results indicated that the grain size became smaller with the increase of the hot-rolling thickness reduction. The nano-indentation creep test results showed that the creep power-law stress exponent was about four, and the creep resistance increased when the hot-rolling thickness reduction increased.